2008
DOI: 10.1016/j.jmb.2008.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of in Vivo and in Vitro Insertion Patterns in Hot E. coli Gene Targets of Transposable Element Mu: Opposing Roles of MuB in Target Capture and Integration

Abstract: Phage Mu transposes promiscuously, employing MuB protein for target capture. MuB forms stable filaments on A/T-rich DNA, and a correlation between preferred MuB binding and Mu integration has been observed. We have investigated the relationship between MuB-binding and Mu insertion into 'hot' and 'cold' Mu targets within the E. coli genome. Although higher binding of MuB to select hot versus cold genes was seen in vivo, the hot genes had an average A/T content and were less preferred targets in vitro, whereas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…8A) (34). Consistent with this model, Mu transposition was observed at the junction of A/T and non-A/T DNA in vitro (97), and in the vicinity rather than within MuB bound regions in vivo (88). Two hot spots for Mu insertion near the bgl locus were also observed to be clustered at the borders of an A/T rich segment (92).…”
Section: Target Site Selectionsupporting
confidence: 57%
See 2 more Smart Citations
“…8A) (34). Consistent with this model, Mu transposition was observed at the junction of A/T and non-A/T DNA in vitro (97), and in the vicinity rather than within MuB bound regions in vivo (88). Two hot spots for Mu insertion near the bgl locus were also observed to be clustered at the borders of an A/T rich segment (92).…”
Section: Target Site Selectionsupporting
confidence: 57%
“…Two hot spots for Mu insertion near the bgl locus were also observed to be clustered at the borders of an A/T rich segment (92). Interestingly, the majority of A/T rich regions were unavailable for MuB binding in vivo because they are occupied by nucleoid proteins such as Fis, which have a similar binding preference (88, 97). Other strongly DNA-bound proteins also occlude Mu insertions (94).…”
Section: Target Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On natural DNA, which can range from 40% to 70% A/T, analysis of MuB binding and Mu insertion patterns is consistent with a fairly interspersed pattern of MuB binding, with insertions being directed to adjacent DNA sites free of MuB [19]. The pattern of Mu insertion within such DNA is unperturbed over a wide range of MuB concentrations.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to facilitating protein polymerization through intra-filament interactions, the ability of the NTD in bridging MuB filaments expands the possibilities of the dynamic association of MuB with the DNA. It has been found that the DNA inside the filament cannot be used as a target DNA for transposition (Ge and Harshey, 2008;Mizuno et al, 2013) and a mechanism was proposed by which the coordinated ATP hydrolysis of several MuB subunits at the filament end could distort the DNA structure, favoring DNA bending and recognition by the transposome (Mizuno et al, 2013). The interaction between MuB filaments bound to nearby DNA sequences could further facilitate the bending of the intermediate sequence or the formation of a special DNA structure, thus assisting target DNA capture by MuA.…”
Section: Discussionmentioning
confidence: 99%